REACTION OF GINGER CULTIVARS AGAINST PHYLLOSTICTA ZINGIBERI CAUSING LEAF SPOT AND ITS MANAGEMENT - K. T. ARUNAKUMARA; C. SATYANARAYANA (The Bioscan, 2015)
Ten Ginger cultivars were tested, during Kharif 2013 and 2014 for their reaction to Phyllosticta zingiberi under field conditions. Humnabad local and Maran cultivars were found moderately resistant and none of them were free from the disease. Among 10 fungicides, 10 botanicals and 6 bio-agents evaluated in in vitro condition against Phyllosticta zingiberi Ramkr, Propiconazole 25 EC (92.30%) followed by Azoxystrobin 25 EC (91.70%), SAAF 75 WP (Mancozeb and Carbendazim) (89.30%), Allium sativum (75.70%) and Trichoderma harzianum (78.80%) recorded the highest inhibition of mycelial growth of Phyllosticta zingiberi. The field evaluation of different fungicides and botanicals during Kharif-2014 indicated that Propiconazole-25EC was recorded minimum PDI of 36.00 and yield of 202q/ha. Azoxystrobin-25EC,Hexaconazole-5EC,SAAF-75WP (Mancozeb-63WP and Carbendazim-12WP),Mancozeb-75WP,Propineb-50WP and Allium sativum cloves extract were next best treatments by recording a PDI of 40.00,45.00,46.00,50.00,55.00 and 60.00 and a yield of 185q/ha,180q/ ha,179q/ha,175q/ha,173q/ha and 169q/ha respectively.Again during Kharif 2015, Propiconazole 25 EC was significantly superior over other treatment and similar trend was observed for other treatments also.